METODE RGEC UNTUK MENILAI KINERJA KEUANGAN PT BANK PANIN SYARIAH, TBK PERIODE 2016-2019 - Roy Seleky; Meiske Wenno (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
PT Bank Panin Dubai Syariah Tbk in 2019 recorded financing growth, but this was not comparable to the bank's profit achievement in that year. The purpose of writing this article is to analyze and evaluate the financial performance of PT Bank Panin Dubai Syariah, Tbk for the period 2016 – 2019 using the RGEC method. The data analysis method used in this study is a quantitative analysis method by calculating, analyzing and interpreting data describing NPF, FDR, GCG, ROA, NOM and CAR. The results of the calculation of the financial performance of PT Panin Bank Dubay Syariah in 2016-2019 are NPF in the